Wildlives : 50 extraordinary animals that made history - Lerwill, Ben (Atheneum Books for Young Readers, 2020)
Presents true tales of fifty animals from around the world who have aided humans with bravery, making discoveries, and showing true friendship with their human companions. Includes the story of Wojtek, the bear who served in the Polish Army during World War II; Streetcat Bob, who befriended struggling musician James Bowen; and Congo, the chimpanzee who learned how to paint. Includes a glossary.